Nitric Oxide Synthesis Metabolites—As Potential Markers in Chronic Kidney Disease in Children - Joanna Piechowicz; Andrzej Gamian; Ositadima Chukwu; Dorota Polak-Jonkisz (Current Issues in Molecular Biology, 2022)
Nitric oxide (NO) is an important signaling molecule for many physiological and pathological processes. Diseases associated with abnormal NO synthesis include cardiovascular diseases, insulin-dependent diabetes, or chronic kidney disease (CKD). The aim of the paper was to evaluate NO synthesis metabolites, i.e., asymmetric dimethylarginine (ADMA), symmetric dimethylarginine (SDMA), dimethylamine (DMA), arginine, citrulline in plasma of patients with different severity of CKD and to seek possible links between these parameters and the development of this disease. Forty-eight CKD children and thirty-three age-matched controls were examined. Patients were divided into groups depending on the CKD stages (Group II-stage II, Group III-stage III, Group IV-stage IV, and Group RRT children on dialysis). To determine the concentrations of the above-mentioned metabolites in plasma liquid chromatography-mass spectrometry was used. There were significant differences observed in levels of ADMA, SDMA, DMA, and citrulline between control vis CKD groups (p values ranging from <0.001 to 0.029). Plasma arginine concentration was also higher in CKD patients compared to the control group but statistically insignificant. ADMA levels in CKD children were statistically significantly higher in relation to particular stages of CKD (RRT vis II stage of CKD: p = 0.01; RRT vis III-IV stages of CKD: p < 0.046). Citrulline levels in CKD children were statistically significantly higher in RRT group vis control (p < 0.001). Children with CKD develop disturbances in most metabolites of NO synthesis. Dialysis children treated show the greatest disturbances of plasma ADMA and citrulline levels. ADMA seems to be a good indicator of the gradual progression of the CKD, which is proved by the negative correlation with eGFR.